Democracy and economy : an inseparable relationship from ancient times to today - Economou, Emmanouil Marios N.; Kyriazis, Nicholas C. (Cambridge Scholars Publishing, 2019)
This text presents a detailed history of democracy, while also considering the modern methodological tools of economic history, institutional economics, and political, social and behavioural sciences, to explain why and how democracy was created, how it evolved and how it progresses. The book provides answers to a number of questions, such as what form of government democracy is, why it was first developed in ancient Greece, why it is that democracy--in order to flourish--requires strong and stable economic structures, and what role political and military organizations play in the shape of these elements. The volume analyses various cases studies drawn from Ancient Greece, Switzerland, England, the United Provinces, France, the USA, Germany and the EU.